The place of environmental education in the family (Journal of Universal Science Research, 2024)
This article highlights the place of environmental education in the family. The authors of the article believe that the spiritual and physical life of a person at all its stages of development is inextricably linked with nature. The main goal of environmental education in a modern family is to form a culture of behavior and social responsibility of their children for nature, which in turn is itself an inexhaustible source of education through its diversity and beauty. It is the beauty of nature in any corner of our planet where a person lives that gives rise to a feeling of love for his Homeland, his home, mother, and people. Man stands at the highest stage of the development of life on earth, but this does not mean that all nature belongs to him, as he arrogantly imagines. Man belongs to nature. He must understand this, learn how to use her wealth rationally and protect her incomparable beauty. Keywords: environmental education, formation, culture, feeling, social, responsibility, source, beauty, nature, rationally, diversity.